The Effect of Adding Expired Sweetened Condensed Milk on the Physical Quality of Rice Straw Silage: Pengaruh Penambahan Susu Kental Manis Kadaluarsa Terhadap Uji Kualitas Fisik Silase Jerami Padi - Elsi Rija; Maulina Novita; Yusuf Mahlil; Putri Zulia Jati; M. Zaki (BPFP Universitas Bengkulu, 2026)
This research aims to determine the physical quality of rice straw silage with the addition of expired sweetened condensed milk regarding color, texture, aroma, presence of mold and pH. The method used in this research was a Completely Randomized Design (CRD) consisting of 5 treatments and 3 replications fermented for 21 days. The treatment details are P0: Rice straw + 0% expired sweetened condensed milk + 0% EM4, P1: Rice straw + 3% expired sweetened condensed milk + 1.5 EM4, P2: Rice straw + 6% expired sweetened condensed milk + 1.5% EM4, P3: Rice straw + 9% Expired sweetened condensed milk + 1.5% EM4, P4: Rice straw + 12% Expired sweetened condensed milk + 1.5% EM4. Parameters observed include color, texture, aroma, presence of mold and pH. The results of this study showed that the addition of expired sweetened condensed milk had no significant effect (P>0.05) on the color of rice straw silage. It had a significant effect (P<0.05) on texture and pH, and a very significant effect (P<0.01) on the aroma and presence of rice straw silage mold. The treatment that provides the best physical quality is the addition of 9% expired sweetened condensed milk because it can improve the texture, making it soft, easy to separate with an average value of (3.31) and gives a slightly sour aroma with an average value of (3.55), gives a brownish green color with an average value of (3.58), provides a little mold with an average value of (3.39), and has an influence on pH which shows an average value of (6.00).